2014
DOI: 10.1093/infdis/jiu539
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Treatment With an Anti-M2e Monoclonal Antibody in Experimental Human Influenza

Abstract: These data indicate that TCN-032 may provide immediate immunity and therapeutic benefit in influenza A infection, with no apparent emergence of resistant virus. TCN-032 was safe with no evidence of immune exacerbation based on serum cytokine expression. Clinicaltrials.gov registry number. NCT01719874.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
104
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(109 citation statements)
references
References 16 publications
4
104
0
1
Order By: Relevance
“…In line with this, passive transfer of mouse and human monoclonal antibodies directed against M2e can protect against influenza A virus challenge (11,(18)(19)(20)(21). It has also been reported that treatment of experimentally challenged human volunteers with a human monoclonal antibody directed against M2e reduces viral replication and clinical symptoms (22).…”
mentioning
confidence: 77%
“…In line with this, passive transfer of mouse and human monoclonal antibodies directed against M2e can protect against influenza A virus challenge (11,(18)(19)(20)(21). It has also been reported that treatment of experimentally challenged human volunteers with a human monoclonal antibody directed against M2e reduces viral replication and clinical symptoms (22).…”
mentioning
confidence: 77%
“…Vaccines that elicit antibody responses against conserved surface-exposed antigens, such as the stem region of influenza hemagglutinin or M2e, can protect against multiple influenza virus subtypes (1). A potential clinical benefit of M2e-based vaccines can be inferred from a challenge study in human volunteers, which showed that injection of human monoclonal antibody (MAb) TCN-032 directed against M2e 1 day after inoculation of an H3N2 influenza virus resulted in reduced clinical signs and virus shedding compared to placebo treatment (2).…”
mentioning
confidence: 99%
“…To address this question, we compared the outcome of both our 2010 placebo group and the 2008 Retroscreen (Retroscreen Ltd., personal communication) placebo group against those reported for placebo groups in other published studies carried out in 2008 (3), 2009 (9), and 2013 (8). These studies were performed according to the same common standard protocol (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The reported postchallenge clinical outcomes for the placebo group of four reported independent clinical trials (3,(7)(8)(9) and one previously unreported study (Retroscreen Ltd., personal communication) were used for the meta-analysis. The placebo agents used in the studies were different, but all the studies were carried out by the same clinical group (Retroscreen Ltd.) and were conducted according to a common challenge protocol ( Fig.…”
Section: Methodsmentioning
confidence: 99%